KECERDASAN EMOSIONAL DOSEN DITINJAU DARI JENIS KELAMIN - Padmaningrum, Regina Tutik (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2018)
The aim of the study was to identify 1) the level of emotional quotient of the lecturers of Mathematics and Natural Sciences based on their gender at various universities in the Province of Yogyakarta, and 2) the differences in the emotional quotient among the lecturers. The study was ex-post facto research. As the research variable, emotional quotient was defined as the scores resulting from the EQ questionnaire to include self emotion knowing, self emotion management, self motivation, others emotion knowing, and relationship construction. The population of the study was designated to be the lecturers of Mathematics and Natural Sciences at various universities in Yogyakarta Province. The sample of the study consisted of 141 lecturers, 72 male and 69 female, taken by purposive random sampling technique. The instrument was the questionnaire adapted from relevant references (Ridwan Saptoto: 2002). Data were analyzed qualitatively by conversion criteria. EQ differences were computed statistically by a t-test. Results showed that the average score of EQ levels of male and female lecturers were 79.6% (very high criteria) and 78.2% (high criteria). The difference (1.4%) was not statistically significant